Recurrence of Precancerous Cervical Lesions After Loop Electrosurgical Excision Procedure (Leep): A Systematic Review - Alifsya Bidarani Widyajayaning Sukma; Tatit Syahadani Alfirdausi (Jurnal Impresi Indonesia, 2026)
To qualitatively synthesize available evidence on recurrence rates of CIN 2/3 following LEEP and risk factors associated with recurrence precancerous cervical lesions. Reputable scientific databases were used to conduct a comprehensive literature search, with a focus on peer-reviewed journals found in PubMed and Scopus. We included cohort studies that reported histologically confirmed CIN2/3 recurrence rates and utilized statistical analysis to identify associated risk factors following LEEP. Key quantitative data on recurrence rates, follow-up duration, and results were critically extracted and synthesized. The study selection process yielded four studies that met the inclusion criteria. All included studies were retrospective in design. The reported incidence of CIN 2/3 recurrence post-LEEP varied widely across studies, ranging from 3,2 % to 9,8%. Most recurrences were detected within the first 12 to 18 months of follow-up. The most potent factor is the persistence of high-risk Human Papillomavirus (HR-HPV) infection post-treatment, showing an exceptionally strong association. Qualitative synthesis identified risk factors of recurrence: (1) persistent post-procedure infection with high-risk Human Papillomavirus (HR-HPV), (2) positive surgical margins, and (3) older patient age. Persistent HR-HPV infection is the most critical determinant governing the recurrence of precancerous cervical lesions after LEEP. These findings strongly advocate for post-treatment surveillance protocols that integrate HR-HPV testing with cytology to accurately stratify risk and ensure prompt, targeted re-intervention for high-risk patients.